In the Flesh and the Gothic Pharmacology of Everyday Life; or Into and Out of the Gothic - Murnane, Barry (Text Matters: A Journal of Literature, Theory and Culture, 2016)
One of the key questions facing Gothic Studies today is that of its migration into and out of its once familiar generic or symbolic modes of representation. The BBC series In the Flesh addresses these concerns against the background of a neoliberal medical culture in which pharmaceutical treatments have become powerful tools of socio-economic normalization, either through inducing passivity or in heightening productivity, generating chemically adapted biomachines tuned to think and produce. But the pharmakon has always been a risky form of normalization, its poisonous mechanisms threatening to undo its helpful patterns by stealth. This essay discusses the pharmacological and medical contexts of the series in which zombies are subjected to medical management and normalized as “PDS sufferers,” thereby locating In the Flesh in terms of an already gothicized neoliberal pharmacology of everyday life. It also enquires how the proximity of the symbolic pharmacology of the series to neoliberal medical discourses and practices actually challenges traditional representational patterns of the Gothic and whether the Gothic can still have a role as an alternative cure to society’s ills.